Padrões alimentares de pacientes hospitalizados com insuficiência cardíaca e a sua relação com fatores sociodemográficos, econômicos e clínicos em Sergipe - Costa, Jamille Oliveira (2022)
Background: The high rates of hospitalization and mortality caused by Heart Failure (HF) have attracted attention from health sectors around the world. In the non-pharmacological treatment, the quality of the food is essential to obtain positive clinical outcomes of this clinical disease. The guidelines focus on recommendations for approaching nutrient intake. However, in recent times, the literature recommends that the relationship between diet and health or illness involve combinations of foods and preparations that represent the synergistic or antagonistic effects of different dietary components. Objectives: To describe the dietary patterns of patients hospitalized for HF decompensation and associate them with demographic, economic, and clinical factors, and the type of care provided in Sergipe. Materials and Methods: Cross- sectional study that is part of the Registry of HR (VICTIM-CHF)” of Aracaju/SE. Prospective data collection took place with all patients hospitalized between April 2018 and February 2021 in cardiology referral hospitals, 2 public and 1 private. The data collected were sociodemographic, clinical, lifestyle, anthropometric and food consumption variables. Daily dietary intake was estimated by applying a semiquantitative food frequency questionnaire. The extraction of dietary patterns, by exploratory factor analysis, was performed after grouping the foods according to the nutritional value and form of preparation into 34 groups. To assess the association between the factorial scores for adherence to the standards and the variables studied, the Mann-Whitney U test was applied. Linear regressions were also performed, considering the dietary pattern (one for each pattern) as a dependent variable. The accepted statistical significance was p < 0.05. All analyzes were performed using the R statistical software. Results: The study included 240 patients hospitalized for HF decompensation, most of them elderly (mean age 61.12±1.06 years), male (52.08%) and attended by the health public system (67.5%). Three dietary patterns were identified, labeled "traditional" (typical foods of the Brazilian northeastern population added to ultra-processed foods), "Mediterranean" (foods recommended by the Mediterranean diet) and "dual" (healthy foods combined with fast and easy-to-prepare foods like snacks, bread, sweets and desserts). Adherence to the “traditional” pattern was greater among men and non-diabetics. The “Mediterranean” was more consumed by the elderly, with partners and a lower income, assisted by the health public system and without hypertension. The “dual” diet pattern had greater adherence by the elderly, self-declared non- black, with higher income, assisted in the private sector and with less impaired functional capacity. It was also observed that being female and being older reduced the average scores of performing the “traditional” pattern. Regarding the type of service, being from the public service reduced the average scores for adhering to the “dual” pattern. Conclusions: Three dietary patterns representative of the population were found, called traditional, Mediterranean and dual, which were associated with demographic, economic and clinical factors. Thus, these standards must be considered in the development of nutritional strategies and recommendations in order to increase adherence to diets that are more protective against cardiovascular diseases.